ANTIMICROBIAL RESISTANCE PATTERNS AND PHENOTYPIC CARBAPENEMASE DETECTION IN CLINICAL PSEUDOMONAS AERUGINOSA ISOLATES - AHUTI PANDYA; RIA KOTECHA; UJALA SAROLA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Pseudomonas aeruginosa is a significant pathogen responsible for hospital-acquired infections. Its capacity for multidrug resistance (MDR) limits therapeutic options and contributes to elevated patient morbidity. This study investigates the frequency of MDR and extensively drug-resistant (XDR) P. aeruginosa isolates and evaluates the effectiveness of phenotypic methods for detecting carbapenemase activity. Methods: A total of 100 P. aeruginosa isolates were collected from various clinical samples over 6 months in a cross-sectional study. Antimicrobial susceptibility testing was conducted using the Kirby–Bauer disk diffusion technique, adhering to the Clinical and Laboratory Standards Institute 2024 standards. Carbapenem-resistant isolates were further analyzed for carbapenemase production using three methods: modified Hodge test (MHT), combined double-disk synergy test (CDDT), and modified carbapenem inactivation method (mCIM)/EDTA-modified carbapenem inactivation method. Results: Out of 100 isolates, 19% were classified as MDR and 24% as XDR. The highest susceptibility was observed with imipenem (79%), followed by meropenem (75%) and piperacillin–tazobactam (67%). Among the 26 carbapenem-resistant isolates, MHT detected carbapenemase production in 46.2%, CDDT in 26.9%, and mCIM in 38.5%. Metallo-β-lactamase production was observed in 34.6% of isolates, whereas 3.8% demonstrated serine- β-lactamase activity. Conclusion: The presence of MDR and XDR P. aeruginosa and substantial carbapenem resistance underscores the importance of consistent antimicrobial surveillance and the implementation of accurate detection techniques such as mCIM. Prompt identification of resistance mechanisms is critical for appropriate therapy and the control of nosocomial infections.